Bioinspired superwettable micropatterns for biosensing. (16th May 2019) - Xu, Tailin; Xu, Li-Ping; Zhang, Xueji; Wang, Shutao
Abstract : The bioinspired micropatterns exhibit outstanding capacity in controlling and patterning microdroplets, which have offered new functionalities and possibilities towards a wide variety of emerging biological and biomedical applications. Abstract : The bioinspired micropatterns exhibit outstanding capacity in controlling and patterning microdroplets, which have offered new functionalities and possibilities towards a wide variety of emerging biological and biomedical applications. By taking the advantages of the microdroplet anchoring ability, enrichment ability, and the accessibility of such bioinspired micropatterns, the selected topic mainly focuses on the important aspects related to (super)wettable surfaces and their emerging sensing applications (DNA, miRNA, proteins, etc. ) by combining them with multiple signal output approaches (fluorescence, colorimetric, SERS, electrochemical, etc. ). In the end, we also provide a personal perspective on the future development, and address the remaining challenges in the commercialization of (super)wettable micropatterns towards biosensing.